PERANCANGAN SISTEM INFORMASI AKADEMIK MADRASAH ALIYAH NEGERI (MAN) 4 KARAWANG BERBASIS WEB - Dian Ardiansyah; Atang Saepudin; Riska Aryanti; Eka Fitriani (Universitas Islam Kuantan Singingi, 2020)
The development of web-based information technology is currently increasing. One of them is the website. The website has the advantage that all the information you want can be easily and cheaply obtained. Madrasah Aliyah Negeri (MAN) Rengasdengklok or now known as MAN 4 Karawang currently processing academic data, especially in processing grades is still very simple, namely only with Microsoft Excel. The presence of this academic information system is expected to help teachers and students get academic information more quickly, easily and cheaply. In building this system the writer uses the waterfall methodology. The design and implementation were carried out with the Dreamweaver programming language and PHP and the database used by PhpMyAdmin. With this academic information system, hopefully it can help to support school performance, especially for processing academic data.